Computer Order Entry System Decreased Use of Sliding Scale Insulin Regimens - Achtmeyer, C. E.; Payne, T. H.; Anawalt, B. D. (Methods of Information in Medicine, 2002)
IntroductionObjectives: Despite evidence documenting their ineffectiveness, sliding scale insulin is a commonly used regimen for glucose management for hospitalized patients with diabetes mellitus. At the Veterans Affairs Puget Sound Medical Center, where computer order entry has been mandated, we tested the hypothesis that an evidence-based minimal intervention order (supplemental insulin only when fasting serum glucoses exceeded 400 mg/dl) would decrease the use of sliding scale insulin orders.Methods: Using a computerized order entry system, providers were initially offered a traditional sliding scale order or their own ad hoc orders for glycemic control of inpatients. After 34 weeks providers were offered a third option; a “minimal intervention order” with supplemental insulin only for glucose >400 mg/dl. We extracted all regular insulin orders and performed a retrospective review of insulin sliding scale orders written between December 1, 1998 and November 16, 1999. We compared the frequency of traditional insulin sliding scale orders before and after the introduction of the minimal intervention order.Results: Nearly all orders in the first 34 weeks were traditional insulin sliding scales. We found a significant decrease in the number of traditional insulin sliding scale orders in the 16 weeks after the introduction of a computerized quick-order for minimal intervention, from 978/1007 (97.1%) to 254/398 (63.8%) (P <0.001).Conclusions: A simple, evidenced-based quick-order in a computer order entry system rapidly and significantly reduced use of sliding scale insulin regimens for glycemic control of inpatients.
Keywords: Medical records systems; computerized; diabetes mellitus; physicians practice patterns; insulin